Women Architects in Portugal: Working in Colonial Africa before the Carnation Revolution (1950–1974) - Milheiro, Ana Vaz (2020)
How did women architects shape a modern world in the late period of Portuguese colonial Africa, just before the Carnation Revolution? The specific role of women in Portugal working in colonial African architectural culture has now started to be addressed by Portuguese and Lusophone-African historiography. During the 1950s, the presence of women in the metropolitan schools of architecture was reduced. Of those who could graduate, few actually worked as architects. Most were absorbed by the commonly feminine roles, resulting from marriage and from the ideal of family promoted by the Estado Novo dictatorship. To the ones that risked prosecution for working outside the family, the option of jobs associated with the feminine universe, such as teaching, was privileged. Among those who were emancipated from this pattern, the majority worked in familiar partnerships, regarded as an extension of marriage. The women architects that follow the husbands in their African emigration often ended up having the opportunities to work in their professional field partly due to the lack of qualified technicians, and to the high demand of commissions. This paper not only seeks to outline a perspective on these women, but also tries to understand the context of their work by presenting two case-studies in the late in the late period of Portuguese Colonisation: Maria Carlota Quintanilha and Maria Emilia Caria.